Integration of Master‘s Studies Graduates into the Labour Market: Analysis of the Results of Sociological Survey - Beresnevičiūtė, Vida; Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2007)
The article is based on the data of the representative sociological survey of the master‘s studies graduates of 2001–2005. The survey was conducted by “RAIT“ company on the order by the Public Policy and Management Institute. The analysis of the sociological survey data of master‘s studies graduates was based on the following major aspects: structural which embraced the analysis of the graduates’ position in the labour market; functional which examined the readiness of the graduates for the labour market, and evaluative which is related to the evaluation of the graduates’ professional integration. The functional analysis of the graduates’ integration into the labour market revealed that only a part of the surveyed graduates consider their studies as facilitating in their preparation for the employment. Two-thirds agree that the master’s studies helped them prepare for their professional activity and guarantee a more successful professional career. A larger part of the graduates thinks that their wages do not comply with their acquired education. The graduates are sure that their education and the professional competence are better valued by the society than the size of their income, material wellbeing and connections. Noting that high self-evaluation is prerogative for successful social integration, it is possible to maintain that the professional studies provided with the basis for more successful social integration.